Purchase order for supply & installation of precast concrete slabs on the pedestals for the roof drainage of BRACU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and NS Construction Limited for supply and installation of precast concrete slabs on the pedestals for Brac University new campus project.